Comparison of Prevalence, Histopathology, and Genetic Relationship of Pneumocystis spp. in Eleven Mammal Families. (March 2022) - Weissenbacher-Lang, C.; Blasi, B.; Bauer, P.; Binanti, D.; Ergin, L.; Fragner, K.; Högler, C.; Högler, T.; Klier, M.; Matt, J.; Nedorost, N.; Silvestri, S.; et al.
Abstract : Purpose: Pneumocystis ( P. ) spp. are a group of highly diversified opportunistic fungi, which are adapted to the lungs of potentially all mammals. Because of its high impact on human health, research has concentrated on humans and rodent models . This study aimed to investigate the prevalence, histopathology, and genetic relationship of P. in livestock, pet and wild mammals. Methods & Materials: FFPE lung tissue samples of 240 Suidae, 104 Muridae, 96 Bovidae, 76 Felidae, 47 Mustelidae, 36 Equidae, 31 Canidae, 23 Camelidae, 21 Cervidae, 18 Pteropodidae and 14 Leporidae were screened by in situ hybridization (ISH) using a universal 18S rRNA probe for P., followed by H&E stain for determining histopathological lesions. Selected samples from 12 animal species were used to evaluate genetic relationships. Results: The highest P . prevalence was detected in Canidae (61%) followed by Mustelidae (55%), Suidae (48%), Bovidae (25%), Leporidae (21%), Cervidae (14%), Equidae (14%), Pteropodidae (11%), Camelidae (9%), Felidae (7%), and Muridae (7%). In all species, the number of cases with high ISH signal density was low. P. could be described for the first time in the following mammalian species: bison, blackbuck, chamois, water buffalo, alpaca, Bactrian camel, badger, marten, otter, skunk, and wolf. For most of the samples, microscopic exam of H&E-stained lung tissues showed minor lesions consistent with an interstitial or granulomatous pneumonia; P. organisms were primarily located within the alveoli by ISH. In a small number of samples with severe infection, P. organisms were also detected on the ciliated respiratory epithelium of bronchioles and bronchi. In only one sample from a sheep, a significantly higher P . organism load was observed within the larger respiratory airways than within the alveoli. The extent of phagocytosis of the fungus by alveolar macrophages varied substantially. The sequences clustered according to the phylogenetic evolution of their host species. Conclusion: The results of the present study underlined the wide distribution of P. within the Mammal class. Prevalence varied substantially, with a low organism load in all samples, suggesting a colonization role in these animals. More comprehensive studies are required to better understand the epidemiology, host specificity and pathogenesis of P.